Educational implications of reading habits in the academic behavior of the university students to distance (Revista Electrónica Calidad en la Educación Superior, 2020)
The article that is presented is contextualized in the research: Exploratory study on reading habits among the student population of the State Distance Learning University (UNED), Costa Rica. Presents aspects related to the educational implications of the reading habits of students in their academic behavior. The above, in a university level at a distance with the characteristics of this educational modality and competencies of academic character expected in the student body; for example, the self-management of learning, relationships of the person teaching and student and the mediation of vocational training, with the instructional use of the different information and communication technologies. Also, reference is made to the reading habits of the student body from its significance and impact on performance and the quality of the preparation in any field of study, with new patterns of what it is to be reader in the university world today. There are those variables of research that can broaden perspectives and analysis on the practice reading comprehension as a challenge in higher education and distance, aspects related with the methodology, participants, instruments and procedure.
Keywords: sity education at a distance; reading habits; academic behavior